SIMULATION-GAME APPROACH AS A BASIS TECHNOLOGIES OF PREPARATION OF FUTURE TEACHERS TO CREATIVE ACTIVITY (Pedagogy of Higher and Secondary Education, 2001)
This article deals with playing technologies in students’ preparing to their professional activity. The author shows the advantage of imitative-playing teaching in activization of training work and development o f creative abilities of teachers to come.